Effect of mineral fillers on the performance, rheological and dynamic viscosity measurements of asphalt mastic. (20th October 2019) - Naveed, Haris; ur Rehman, Zia; Hassan Khan, Ammad; Qamar, Sabih; Akhtar, Majid Niaz
Highlights: Mechanical behavior of the binder using stone dust, brick dust and fly ash Class F were evaluated. Rutting factor, dynamic viscosity, short term aging and long-term aging study from PAV were investigated. Best performance against rutting as compared to stone dust and brick dust were determined. Dynamic viscosity was improved at 58 °C, 64 °C, 70 °C and 76 °C respectively. Abstract: The principal objective involved in this research is to explore the mechanical behaviour of the binder using different mineral fillers such as stone dust (SD), brick dust (BD) and fly ash Class F (FA). Currently, a large quantity of roads is being constructed under the China-Pakistan Economic Corridor (CPEC) project. It is a major concern for quality of road to with stand heavy loads. For the investigation of the quality of roads, it is mandatory to evaluate the behaviour of mineral fillers addition in asphalt mastic. Fatigue cracking, thermal cracking and permanent deformation have been found a major common distress in the construction of road networks. In this study, the behaviour of mineral fillers such as stone dust, brick dust and fly ash Class F was investigated. In flexible pavements, these mineral fillers with different concentrations such as 0%, 3%, 5% and 7% were used. Rheological, Energy dispersive X-ray (EDX) and scanning electron microscopy (SEM) were utilized to find out the effect of mineral fillers as doping agents in asphalt mastic. Mechanical testing was done on dynamic shear rheometer (DSR), rotational viscometer (RV), rolling thin film oven (RTFO) and pressure aging vessel (PAV). Rutting factor G*/Sin (б) from DSR, dynamic viscosity (ἠ) from RV, short term aging study from RTFO and long-term aging study from PAV were investigated. The micro structural investigations showed that cracks were reduced using mineral fillers which may be due to the even distributions of particles. Rheological studies of modified binders with fly ash Class F revealed best performance against rutting as compared to stone dust and brick dust. However, the addition of 7% fly ash Class F showed the improvement of 92.17% in rutting factor. In addition, the dynamic viscosity of all three mineral based mixtures were improved at 58 °C, 64 °C, 70 °C and 76 °C respectively. The current research reported the low cost, improved performance and good environmental impacts of mineral fillers in asphalt mastic.